Studi Literatur Penetapan Kadar Fenolik Ekstrak Etanol Daun Turi (Sesbania grandiflora L) secara Spektrofotometri UV-';Vis - aenung, nurul; Baits, Muzakkir; Trihadi, Andi (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
Turi plant (Sesbania grandiflora L) is a fabaceae plant that is widely used by the local community as a medicine for sprains, wounds and bruises.Turi plants contain active compounds of alkaloids, flavonoids, saponins, triterpenoids, phenolics and tannins. The purpose of this study was to determine how much phenolic content contained in the ethanol extract of Turi leaves using UV-Vis Spectrophotometry . The research method used is the Literature Review method by collecting journals conducted online using Google and Google Scholar data bases, then selected 5 journals in accordance with the criteria in the study of literature. Based on the results of research from 5 journals it can be concluded that the ethanol extract of turi leaves has different levels in a row, namely 3,7± 0,44 mg/g, 8,9 ± 1,35 mg, 1445,9 ± 49,33 µg, 88,56 ± 0,09 mg/g dan 0,137 mg.